2021
DOI: 10.1016/j.bbih.2021.100255
|View full text |Cite
|
Sign up to set email alerts
|

Boosting nitric oxide in stress and respiratory infection: Potential relevance for asthma and COVID-19

Abstract: Nitric oxide (NO) is a ubiquitous signaling molecule that is critical for supporting a plethora of processes in biological organisms. Among these, its role in the innate immune system as a first line of defense against pathogens has received less attention. In asthma, levels of exhaled NO have been utilized as a window into airway inflammation caused by allergic processes. However, respiratory infections count among the most important triggers of disease exacerbations. Among the multitude of factors that affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 183 publications
0
17
0
Order By: Relevance
“…Elevated CCL-11 [ 82 , 83 ] plasma levels were significantly higher in all COVID infected patient groups than healthy donors and have been reported in other studies [ 84 ]. A recent study [ 86 ] suggested eosinophilic (≥ 150 cells/μL of blood) asthmatic patients (Th2-phenotype) with elevated IL-13 levels infected with COVID-19 were associated with decreased hospital admissions and less severe outcomes. Furthermore, IL-13 was reported to reduce ACE2 expression and increase TMPRSS2 expression in bronchial epithelial cells ex vivo in asthmatic and nonasthmatic atopic groups [ 85 ].…”
Section: Allergic-asthma and Hypoxiamentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated CCL-11 [ 82 , 83 ] plasma levels were significantly higher in all COVID infected patient groups than healthy donors and have been reported in other studies [ 84 ]. A recent study [ 86 ] suggested eosinophilic (≥ 150 cells/μL of blood) asthmatic patients (Th2-phenotype) with elevated IL-13 levels infected with COVID-19 were associated with decreased hospital admissions and less severe outcomes. Furthermore, IL-13 was reported to reduce ACE2 expression and increase TMPRSS2 expression in bronchial epithelial cells ex vivo in asthmatic and nonasthmatic atopic groups [ 85 ].…”
Section: Allergic-asthma and Hypoxiamentioning
confidence: 99%
“…Blood eosinophils are predominantly mediated by IL-5 and in part by IL-13, whereas fractional exhaled nitric oxide (FeNO) is mediated by IL-13. However, the function of elevated NO levels in asthma remains ambiguous, with both detrimental (exacerbation) as well as beneficial (antiviral) effects of airway NO being reported [ 86 , 87 ]. For example, data from human eosinophils suggest direct antiviral binding capacity may be reduced in asthma and is shown to correlate with disease severity [ 88 ].…”
Section: Allergic-asthma and Hypoxiamentioning
confidence: 99%
See 1 more Smart Citation
“…Coronavirus-like SARS-CoV-1, MERS-CoV and SARS-CoV-2, which have been shown to infect endothelial cells, lead to a decrease in endothelial NO [ 14 ]. Indeed, SARS-CoV-2 infection seems to disrupt the signaling for endothelial NO production [ 36 ] and significantly decreased endothelial NO levels were measured in patients with COVID-19 [ 37 ]. Angiotensin-converting enzyme 2 (ACE2), which is the virus gateway into cells, converts angiotensin II to angiotensin 1-7, activating a pathway that increases NO production, among other effects.…”
Section: Role Of No In Vascular Endotheliummentioning
confidence: 99%
“…Among its antimicrobial effects, NO has shown antiviral effects against DNA and RNA viruses, including SARS-CoV-2, by partially inhibiting virus replication ( Rolim et al, 2019 ; Akaberi et al, 2020 ; Pieretti et al, 2021 ). However, it has been shown that viral activity can also compromise host NO production ( Ritz et al, 2021 ). Finally, NO is an important modulator of epithelial ciliary beating, important for the clearance of pathogens, through the activation of the sGC-GMPc-PKG pathway ( Li et al, 2000 ).…”
Section: Role Of Nitric Oxide On the Regulation Of Immune Responsesmentioning
confidence: 99%